Anorexia and bulimia in relation to ulcerative colitis: a Mendelian randomization study - Su, Qiang; Li, Jian; Lu, Yun; Wu, Min; Liang, Jiang; An, Zhenxiang (Frontiers in Nutrition, 2024)
Background: Evidence for anorexia and bulimia in relation to the risk of ulcerative colitis (UC) is limited and inconsistent. The objective of this research was to utilize bi-directional, two-sample Mendelian randomization (MR) analysis to predict the causal association between anorexia nervosa and bulimia nervosa with UC.Methods:The genome-wide association studies (GWAS) provided data for anorexia and bulimia from the UK Biobank,utilizing single-nucleotide polymorphisms (SNP) as instrumental variables. Additionally, genetic associations with UC were collected from various sources including the FinnGen Biobank,the UK Biobank and theInflammatory Bowel Disease Genetics Consortium(IIBDGC). The main analytical approach utilized in this study was the inverse-variance-weighted (IVW) method. To evaluate horizontal pleiotropy, the researchers conducted MR-Egger regression and MR-PRESSO global test analyses. Additionally, heterogeneity was assessed using the Cochrans Q test.Results: This study found a negative association between genetically predicted bulimia (OR = 0.943, 95% CI: 0.893-0.996; p=0.034) and the risk of UC in the IIBDGC dataset, indicating that individuals with bulimia have approximately a 5.7% lower risk of developing UC. No association was observed in the other two datasets.Conversely, genetically predicted anorexia was not found to be causally associated with UC. In bi-directional Mendelian randomization, UC from the IIBDGC dataset was negatively associated with the risk of anorexia (OR = 0.877, 95% CI: 0.797-0.965; p=0.007), suggesting that UC patients have approximately a 12.3% lower risk of developing anorexia, but not causally associated with bulimia.Conclusions: Genetically predicted bulimia may have a negative association with the onset of UC, while genetically predicted anorexia does not show a causal relationship with the development of UC. Conversely, genetically predicted UC may have a negative association with the development of anorexia.